ANALISIS STRATEGI PEMASARAN PRODUK DALAM MENINGKATKAN VOLEME PENJUALAN PADA KELOMPOK USAHA KAIN TENUN LARSASAM, EBSIHA DAN AWAY ERAS DI KOTA SAUMLAKI - Amtai Alaslan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Ikat Woven Fabric is one of the traditional woven fabrics of the community that has been passed down from generation to generation and has a fairly high economic value in the Tanimbar Islands Regency. Along with that, business actors must also be able to take advantage of it by planning their product marketing strategies well in facing today's competition. Entrepreneurs are required to pay more attention to consumer needs and maintain product quality at a price. But in reality the marketing strategy used is still very minimal and simple and the quality of the product is not in line with consumer expectations which results in uncertain and unpromising income. This study aims for the Marketing Strategy of Woven Fabrics in Increasing Sales Volume at the Lar Sasam Weaving Fabric Business Group, the Ebsiha Weaving Fabric Business Group and the Away Eras Weaving Business Group in Quantitative Descriptions by conducting observations, interviews and distributing questionnaires. The data analysis technique used is simple linear regression analysis classical assumption test, statistical test, return to scale and using the coefficient of determination (R2) using the SPSS program.